2011
DOI: 10.1007/s00134-011-2240-2
|View full text |Cite
|
Sign up to set email alerts
|

Dyskalaemia associated with thiopentone barbiturate coma for refractory intracranial hypertension: a case series

Abstract: Hypokalaemia and hyperkalaemia are frequently associated with induction and cessation of thiopentone barbiturate coma. Serum potassium levels must be monitored vigilantly. Patients who develop hypokalaemia and receive large potassium replacement may be at greater risk of hyperkalaemia on cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…Thus, it seems highly unlikely that mannitol administration alone caused the profound electrolyte disorders, although it may have been a contributing factor in some patients. Barbiturate and hypothermia therapy is recommended for control of refractory intracranial hypertension [20] and associated with hypokalaemia [21] and hypophosphataemia [22,23], but they were not used in our population.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems highly unlikely that mannitol administration alone caused the profound electrolyte disorders, although it may have been a contributing factor in some patients. Barbiturate and hypothermia therapy is recommended for control of refractory intracranial hypertension [20] and associated with hypokalaemia [21] and hypophosphataemia [22,23], but they were not used in our population.…”
Section: Discussionmentioning
confidence: 99%
“…However, the real incidence and characteristics of dyskalaemia during and after barbiturate coma have not been well described. Ng et al [55] performed a retrospective review of all 47 patients who received barbiturate therapy for refractory HICP during an 18-month period in a neurosurgical ICU. 89.4% of the barbiturate patients’ cohort developed hypokalaemia after the induction of barbiturate therapy.…”
Section: Neurologymentioning
confidence: 99%
“…In another recent retrospective study, Ng et al reported that 89.4% of patients on thiopentone BCT for refractory intracranial hypertension developed hypokalaemia after induction of the therapy and severe hypokalaemia was reported in only 23.4% of patients. In this study, 34% of patients developed hyperkalaemia during the weaning of BCT (4).…”
Section: Figure 1 Ct Scan Of the Brain On Admissionmentioning
confidence: 55%
“…This report suggested that a lower potassium replacement target threshold of 3.0 mmol/l might be appropriate in the absence of cardiac arrhythmias. Controlled weaning of BCT, instead of abrupt termination, was recommended, and frequent serum potassium monitoring up to 72 hours following cessation is warranted (4). In other reports that applied hyperkalaemia event following the cessation of BCT may be due to the reduction of barbiturateinduced Na + -K + -ATPase activity, resulting in extracellular potassium redistribution (5).…”
Section: Discussionmentioning
confidence: 99%